Pasting properties of buckwheat, rice and maize flours and textural properties of their gels: effect of ascorbic acid concentration - Yildiz, O.; Toker, O. S.; Yuksel, F.; Cavus, M.; Ceylan, M. M.; Yurt, B. (WAGENINGEN ACADEMIC PUBLISHERS, 2017)
In the present study, the effect of ascorbic acid addition on the pasting properties of several gluten-free flours, namely buckwheat, maize and rice flours, and textural properties of their gels were also investigated. Pasting curves of control flour and 10 mg/kg ascorbic acid-including flour were found to be very similar to each other. However, higher levels of ascorbic acid significantly influenced the magnitude of all pasting parameters such as peak viscosity, trough viscosity, breakdown viscosity, final viscosity, setback viscosity, peak time and pasting temperature. Regarding textural properties specifying machinability of the doughs, ascorbic acid addition also generally influenced textural characteristics such as hardness, adhesiveness, springiness, cohesiveness, gumminess, chewiness and resilience parameters of the samples. According to the results, the ascorbic acid level to be used with the gluten-free flour should be adjusted carefully with regard to pasting and textural parameters. Ascorbic acid addition level directly affected the quality of the end products, determining consumer preference.
Keywords: gluten-free; ascorbic acid; pasting properties; textural properties; gels; CASSAVA STARCH; GLUTEN PROTEINS; WHEAT; DOUGH; QUALITY; BREAD; CORN; GELATINIZATION; OPTIMIZATION; PARAMETERS; Food Science & Technology